Immune Correlates of Disease Progression in Linked HIV-1 Infection - Tuen, Michael; Bimela, Jude S.; Banin, Andrew N.; Ding, Shilei; Harkins, Gordon W.; Weiss, Svenja; Itri, Vincenza; Durham, Allison R.; Porcella, Stephen F.; Soni, Sonal; Mayr, Luzia; Meli, Josephine; et al. (Frontiers in Immunology, 2019)
Genetic and immunologic analyses of epidemiologically-linked HIV transmission enable insights into the impact of immune responses on clinical outcomes. Human vaccine trials and animal studies of HIV-1 infection have suggested immune correlates of protection, however, their role in natural infection in terms of protection from disease progression is mostly unknown. Four HIV-1+ Cameroonian individuals, three of them epidemiologically-linked in a polygamous heterosexual relationship and one incidence-matched case, were studied over 15 years for heterologous and cross-neutralizing antibody responses, antibody binding, IgA/IgG levels, antibody-dependent cellular cytotoxicity (ADCC), viral evolution, Env epitopes, and host factors including HLA-I alleles. Despite viral infection with related strains, the members of the transmission cluster experienced contrasting clinical outcomes including cases of rapid progression and long-term non-progression in the absence of strongly protective HLA-I or CCR5Δ32 alleles. Slower progression and higher CD4/CD8 ratios were associated with enhanced IgG antibody binding to native Env and stronger V1V2 antibody binding responses in the presence of viruses with residue K169 in V2. ADCC against cells expressing native CD4-exposed Env in combination with low Env-specific IgA/IgG ratios correlated with better clinical outcome. This data set highlights for the first time that V1V2-directed antibody responses and ADCC in the presence of low plasma IgA/IgG ratios can correlate with clinical outcome in natural infection. These parameters are comparable to the major correlates of protection, identified post-hoc in the RV144 vaccine trial; thus they may also modulate the rate of clinical progression once infected. The observation that ADCC against cells expressing CD4-exposed Env more strongly correlated with delayed disease progression compared with ADCC against cells expressing wild-type Env suggests a vital role for antibodies targeting open Env conformations in protective antibody-mediated immune responses in natural infection. The findings illustrate the potential of immune correlate analysis in natural infection to guide vaccine development.